2004
DOI: 10.1111/j.0906-7590.2004.03731.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and adult plant performance of forest herbs in three contrasting habitats

Abstract: M. 2004. Population structure and adult plant performance of forest herbs in three contrasting habitats. Á/ Ecography 27: 225 Á/241.In Flanders, forests have been subjected to subsequent periods of reclamation and reforestation, leading to a mosaic of forest patches of various ages and with different abiotic conditions, depending on the duration and intensity of the past agricultural activities. While extensive research has been done on the relative importance of dispersal limitation and establishment limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 58 publications
7
82
1
1
Order By: Relevance
“…Endels et al 2004;Verheyen and Hermy 2004;Baeten et al 2009). The vegetative traits (except for A. nemorosa) were: total number of leaves, leaf length and total aboveground dry biomass.…”
Section: Measurement Of Performance and P Uptakementioning
confidence: 99%
See 2 more Smart Citations
“…Endels et al 2004;Verheyen and Hermy 2004;Baeten et al 2009). The vegetative traits (except for A. nemorosa) were: total number of leaves, leaf length and total aboveground dry biomass.…”
Section: Measurement Of Performance and P Uptakementioning
confidence: 99%
“…In this introduction experiment, G. urbanum actually did perform better and persisted in P-enriched post-agricultural sites (cf. Endels et al 2004), so there must be environmental variables other than P that additionally affect performance (e.g., light availability). On the other hand, P. elatior indeed had the intrinsic ability to show higher performance in P-enriched post-agricultural sites , but due to indirect effects such as low longevity and competition with opportunistically growing herbs taking advantage of the high P availability (e.g., Urtica dioica L.: Pigott and Taylor 1964;Hipps et al 2005;Taylor 2009), the species could not maintain viable populations (Baeten et al 2009).…”
Section: Vegetative and Regenerative Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that arable soils are suitable for colonization as soon as a shading canopy controls competition from weeds (cf. Endels et al 2004). However, in areas with heavy eutrophication (N, P), competition from species such as Urtica dioica may have a negative effect (Honnay, Hermy & Coppin 1999;Verheyen & Hermy 2001a;Hipps et al 2005).…”
Section: Former Land Usementioning
confidence: 99%
“…growth) of a given species may differ in habitats whose quality has been modified by former human practices. Indeed, several studies suggest that past land use can enhance plant performance (Donohue et al 2000;Endels et al 2004;, while others have found the opposite pattern (Vellend 2005).…”
Section: Introductionmentioning
confidence: 99%